Parasitoids of Dipteran leafminers, Diglyphus spp. (Insecta: Hymenoptera: Eulophidae) - Jian Li; Dakshina R. Seal (EDIS, 2011)
This 3-page illustrated fact sheet describes these promising biological control agents for agromyzid leafminers (Diptera: Agromyzidae) — distribution, description, hosts, and economic importance. Includes references. Written by Jian Li and Dakshina R. Seal, Published by the UF Department of Entomology and Nematology as part of the Featured Creatures Collection, December 2010.